The percutaneous learning curve of 3rd generation minimally-invasive Chevron and Akin osteotomy (MICA). Issue 8 (December 2022) - Toepfer, Andreas; Strässle, Michael
Abstract: Background: Minimally-invasive Chevron and Akin osteotomy (MICA) represents the third-generation percutaneous hallux valgus surgery which is characterized by an extra-articular osteotomy, stable internal fixation and a high potential for correction. Compared to other percutaneous techniques of the foot, MICA is generally regarded as an advanced and demanding surgical procedure with a flat learning curve. The aim of this study is to analyze a single-surgeons experience with his first 50 consecutive MICA procedures. Methods: Between May 2018 and February 2021, 50 consecutive MICA procedures performed by the author with the "K-wires-First technique" were prospectively analyzed focusing on surgery duration, number of fluoroscopies, correction results and surgery-associated complications. A modification of the original MICA technique as described by its inaugurators Redfern and Vernois allows the use of a standard-sized C-arm and aims to reduce revison rates and conversion to open surgery by placing the guidewires prior to performing the osteotomy. Results: The average surgery time for all MICA procedures was 46.8 min (SD 12.1, range 31–90 min). The average amount of fluoro shots required to perform MICA was n = 126.6 (SD 40.8, range 65–231). Comparing the preoperative and 6-week postoperative radiographs, the IMA decreased after MICA by a mean of 10.8° from 16.2° to 5.4° and the HVA by a mean of 22.1° from 30.6° to 8.5°. One case required intraoperative conversion to open hallux correction. There were 4 feet in three patients with secondary screw removal of the Chevron fixation due to prominent proximal screw tips. Conclusions: Although the learning curve of 3rd generation MICA is flat and requires specific training and intensive practice, the rate of complications is not elevated compared to other percutaneous hallux valgus techniques. Strict adherence to the principles of 3rd generation MICA with stable fixation and meticulous intraoperative control of each surgical step helps to reduce surgery-associated complications. The learning curve showed a continous improvement in regard to surgery time and use of fluoroscopy. After 40 procedures, the surgery time consistently dropped under 45 min and required less than 100 fluoro-shots. The modified surgical technique may help reduce Chevron screw mal-positioning when using large C-arm fluoroscopy for this procedure. Highlights: 3rd generation MICA is regarded to be a demanding surgical technique for the percutaneous correction of hallux valgus deformity. We analyze the learning curve of 50 consecutive, single-surgeon cases, including intraop parameters, radiological correction and surgery-related complications. The characteristics of the learning curve and the relationship between the number of surgeries and the level of proficiency achieved are discussed. The learning curve of 3rd generation MICA is flat and requires specific training and intensive practice. Sufficient correction can be achieved from the start even for severe deformities. Surgery duration and the number of fluoroscopies will be elevated in the beginning. After 40 procedures, the surgery time consistently dropped under 45min. and required less than 100 fluoroscopies in our series. The modified K-wires first technique safely allows the use of a standard-sized C-arm for fluoroscopy and aims to reduce screw malpositioning.